Diversidade e distribuição espacial de comunidades de macroinvertebrados aquáticos em áreas de cultivo de arroz e banhados no extremo sul do Brasil - Pires, Mateus Marques (2013)
The role of rice fields in representing alternative refugees for wetland-expelled macroinvertebrates, in various scales, was assessed in southern Brazil. It is expected that rice fields sustain a representative version, although poorer, of wetland s macroinvertebrate fauna. Sampling was carried out in three different areas from the Central Depression in the State of Rio Grande do Sul, away hundreds of kilometers from each other. Wetlands and rice fields were simultaneously sampled. Richness was found to be equivalent in both environments. Macroinvertebrate communities composition and taxonomic structure were different at both environments. In rice fields, active dispersal taxa were more common, suggesting that the maintenance of a dry-phase at growth areas during intercrop season favors colonization by these taxa. In wetlands, regional scale was responsible for the greatest contribution to macroinvertebrate diversity. Though, at intermediate-scale (within-region), rice fields presented higher diversity than wetlands, due to different cultivation systems and growth phases of the culture. Drainage practices together with climatic changes affecting study area, which have caused longer drying periods, held up for differences in communities composition and taxonomic structure at both environments. Yet the influence of study scales was more related to wetland s environmental heterogeneity, opposing to rice field lesscomplex environmental structure.